EVALUACIÓN DE LA CAPACIDAD ADYUVANTE DEL GINSENÓSIDO RG1 EN RATONES BALB/C INMUNIZADOS CON UN LISADO DE Staphylococcus aureus (FAVE Sección Ciencias Veterinarias, 2021)
Rg1 ginsenoside, the main active compound of Panax ginseng extract, could be a promising vaccine adjuvant against Staphylococcus aureusbovine mastitis. The aim was to evaluate the adjuvant effects of Rg1 combined with liposomes or alone against S. aureus lysate from bovine mastitis in mice. Female Balb/c mice were divided into 4 groups: S. aureus Lysate + IFA (Group I), S. aureus lysate + liposomes (Group II), S. aureus lysate + Rg1 (Group III) and S. aureus lysate + liposomes + Rg1 (Group IV). All mice were subcutaneously immunized with all formulations 3 times at 2-weeks intervals. Humoral response was evaluated by indirect IgG ELISA assay in plasma collected at the end of the assay. Cellular response was evaluated by MTT kit assay in spleen cells from immunized mice. Groups I and IV showed higher IgG values than groups II and III (p < 0.05). Groups I and II showed higher proliferation values than groups III and IV (p < 0.05). The Rg1-liposome combination increased S. aureus-specific IgG production. However, Rg1 was not able to stimulate lymphocyte proliferation from immunized mice, possibly due to the short S. aureus-specific stimulation time. New assays with different experimental conditions are needed to elucidate adjuvant effects of Rg1 in a murine model.